Reading Strategies Used by Teachers in Teaching Reading in EFL Class - Wa Ode Hartati; Citra Prasiska Puspita Tohamba; Faridawati Faridawati (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The purpose of these researchers is to determine the implementation of reading strategies in the classroom used by English teachers at stage junior high school in kulisusu utara. These researchers use a qualitative design, employing observation and interview instruments. The subject of this research was an English language teacher who has taught English for five years. The researchers' data were analyzed using Miles and Huberman's (2014) qualitative data analysis. The research results show that the English teacher has implemented several reading strategies in class. In the pre-reading, the teacher uses brainstorming, encourages the use of dictionaries and discusses text types. While reading, the teacher uses reading aloud and Jigsaw and uses pictures. Post-reading teachers use evaluating comprehension, in particular, tasks, Clarifying and Justifying Student Answers, Questioning Specific Information, and Reviewing Strategies. The additional benefits include: improved comprehension, increased vocabulary, enhanced critical thinking skills, and improved concentration. This study adopts a qualitative approach, and data collection methods such as observation, interviews, and documentation are employed. Data analysis involves data collection, data reduction, data display and conclusion drawing. Based on the results of research conducted at a stage junior high school in kulisusu utara, the teacher uses a variety of different strategies with the aim of making it easy for students to understand the material. The teacher once taught without using any strategies. Most students are not serious about learning and make a lot of noise. So, the teacher often uses strategies. Using strategi reading is very beneficial for students. Apart from increasing learning concentration, it can also foster students' interest in reading.